1980
DOI: 10.7326/0003-4819-92-1-59
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Insulin Absorption and in Blood Glucose Control Associated with Varying Insulin Injection Sites in Diabetic Patients

Abstract: In seven insulin-dependent diabetic subjects the disappearance rate of 125I-labelled short-acting insulin from injection sites in the abdominal wall was 86% greater than from the leg (P less than 0.005) and 30% greater than from the arm (P less than 0.05). Absorption from the arm was 40% greater than from the leg (P less than 0.05). The postprandial rise in plasma glucose concentration varied inversely with the rate of insulin absorption and was 30 to 50 mg/dL less after abdominal than after leg injection; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(59 citation statements)
references
References 12 publications
6
52
0
1
Order By: Relevance
“…7 However, no differences in insulin absorption were found between superficial and deep subcutaneous adipose tissue. 12,13 It has been shown that the subcutaneous absorption of insulin varies according to adipose tissue depots, in nondiabetic 14 and diabetic 12,13,15 subjects. These differences have been found to correlate with blood flow in some studies [16][17][18][19] but not others.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, no differences in insulin absorption were found between superficial and deep subcutaneous adipose tissue. 12,13 It has been shown that the subcutaneous absorption of insulin varies according to adipose tissue depots, in nondiabetic 14 and diabetic 12,13,15 subjects. These differences have been found to correlate with blood flow in some studies [16][17][18][19] but not others.…”
Section: Introductionmentioning
confidence: 99%
“…When the effect is small, it may go unnoticed, which is perhaps why it has not been previously reported in relation to antipsychotic treatment. The analogous effect has been well documented, however, in the context of insulin administration in patients with diabetes mellitus [14,15]. Exercise involving an extremity that is the site of insulin injection increases the absorption from the injection site and consequently increases systemic bioavailability of insulin.…”
Section: Depots and Blood Flowmentioning
confidence: 97%
“…Thus, the purpose of the bolus component is to provide insulin delivery adequately timed to the absorption of the meal, whereas the purpose of the basal component is to provide adequate insulinisation during the night time and between meals. Obviously, insulin delivery depends on the absorption rate of the injected insulin and this has been demonstrated to vary considerably between different anatomical regions [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the purpose of the bolus component is to provide insulin delivery adequately timed to the absorption of the meal, whereas the purpose of the basal component is to provide adequate insulinisation during the night time and between meals. Obviously, insulin delivery depends on the absorption rate of the injected insulin and this has been demonstrated to vary considerably between different anatomical regions [2][3][4][5][6][7][8][9][10][11][12].It has been shown, that the preferred injection site for NPH insulin is the subcutaneous (s.c.) tissue of the thigh [8,[10][11][12]. Thus, this injection site produces the most constant insulin absorption rate with the smallest peak in plasma insulin [8,[10][11][12].…”
mentioning
confidence: 99%
See 1 more Smart Citation